IMPLEMENTASI MODEL PROJECT BASED LEARNING PADA SISWA SD NEGERI 7 WONOGIRI - Sri Mulyati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2020)
This study aims to describe the improvement of learning outcomes in grouping building spaces using a project-based learning model for grade 1A students at SD Negeri 7 Wonogiri semester 1.The subjects of this classroom action research were grade 1A SD students. Negeri 7 Wonogiri, totaling 29 students, consisting of 16 male students and 13 female students. The research was conducted in semester 1. Data collection about the quality of the learning process using observation instruments, and data about learning outcomes using learning outcome test instruments. The data analysis used an interactive descriptive analysis model. The research was conducted in two cycles, each cycle consisting of planning, action, observation and reflection stages. The results showed that there was an increase in the completeness of learning outcomes to recognize space using various concrete objects from pre-cycle 44.83% (less), 71.41% (less) in cycle 1, and to 89.66% (good) in cycle 2, and The learning outcomes classify space shapes using various concrete objects from pre-cycle 41.03% (less), to 44.83% (less) in cycle 1, and to 82.76% (sufficient) in cycle 2.